Research Progress of Dual-energy CT in Diagnosis and Evaluation of Curative Effect of Liver Cancer: A Review - Cao, Mingtai; Qiao, Yumiao; Gao, Xukun; Liu, Xinyi; Yang, Airu; Fan, Rui; Zhou, Boqi; Huang, Bin; Cao, Yuntai (Current Medical Imaging, 2025)
Primary liver cancer is the sixth most common cancer and the third leading cause of cancer deaths worldwide, with over 900,000 new cases and more than 800,000 deaths annually. Conventional imaging techniques have improved the diagnosis and assessment of treatment response in patients with Hepatocellular Carcinoma (HCC), but they have many limitations. Introducing Dual-Energy Computed Tomography (DECT) into clinical practice offers an opportunity to address these issues. DECT has unique advantages in diagnosing and evaluating the efficacy of HCC treatment. It can provide quantitative information on various substances and, through multi-parameter and quantitative parameter analysis, can be used for early detection of HCC, identification of benign and malignant lesions, and monitoring of lymph node metastasis and Microvascular Invasion (MVI). Additionally, DECT provides valuable information for evaluating therapeutic efficacy. This review covers the imaging principles of DECT, including its basic principles, scanner design modes, and Image Reconstruction (IR) techniques. It then describes the research progress of DECT in diagnosing HCC and evaluating treatment efficacy. Finally, it briefly discusses some limitations of DECT and its future development directions.
Keywords: Accurate diagnosis